Sidelink communication technology enhancement and standardization evolution for C-V2X - ZHAO Rui; WEN Xiaoran; ZHENG Shilei; ZHOU Xiaoxing; XI Yifan; LIU Yanqiang; HU Jinling (Dianxin kexue)
With the rapid development of intelligent transportation systems, sidelink communication technology for cellular vehicle-to-everything (C-V2X) has become the key technology to enable vehicle-to-vehicle, vehicle-to-infrastructure, and vehicle-to-pedestrian communications. 3rd Generation Partnership Project (3GPP) has finished research on sidelink communication technology enhancement, aiming to meet the diverse needs of V2X services, and is actively advancing research and standardization on 6G evolution technologies such as integrated sensing and communication (ISAC), artificial intelligence and machine learning (AI/ML). The development trends of sidelink communication technology in C-V2X were firstly introduced. Then, the key evolution points of 3GPP Release 18 sidelink communication technology were discussed. Finally, considering the research on 6G technology in 3GPP Release 19, a perspective on the standard future development direction of C-V2X was provided.